A Comparative Review of PSA, PSMA PET, and PCA3 Biomarkers in Prostate Cancer Diagnosis: Effectiveness, Cost, and Safety Analysis - Wijaya, Jesselyn; Alexandrena Maive Putri Adya; Jason Oktavian Hartanto; Rizky Amanda Putri; Dinda Rachma Harlisa; Rabhindra Javier Hariri Darussalam (Universitas Airlangga, 2024)
ABSTRACT Background: Prostate cancer is the third most common urological cancer among men in Indonesia, with an incidence rate of 14.8 per 100,000 population in 2012. PSA has been a cornerstone of diagnosis, however its low specificity in distinguishing prostate cancer from other urological malignancies, is followed by study of other biomarkers such as PSMA and PCA3. PSMA and PCA3, either as a single marker or in combination with PSA, has the potential to enhance diagnostic accuracy, aid in risk assessment, and support treatment decision-making. Results : The overall diagnostic accuracy, as indicated by the AUC integrating sensitivity and specificity, shows that PCA3 and PSMA have higher AUC values compared to PSA. Combining PSA with PSMA, PCA3, or both demonstrated promising potential for prostate cancer diagnosis when compared to PSA alone. PSA shows slightly higher sensitivity, supporting its role as a screening tool, while PSMA PET offers better specificity than conventional imaging for detecting advanced prostate cancer, albeit at a higher cost. Meanwhile, PCA3, a urinary biomarker, surpasses PSA in specificity, effectively reducing unnecessary biopsies with a safer, non-invasive approach. Summary : PSA remains the standard diagnostic biomarker for prostate cancer screening. Its low specificity may result in unnecessary biopsies. Other biomarkers like PSMA and PCA3 may be more appropriate for specific patient situations than PSA, with PCA3 being the least invasive procedure and PSMA PET being the most expensive. A multimodal approach combining PSA with PSMA or PCA3 shows significantly higher accuracy than PSA alone, improving diagnostic chances and reducing the risk of overdiagnosis.